The Ivy League-Big Ten epidemiology of concussion study: A report on methods and first findings - Putukian, M.; D`Alonzo, B. A.; Campbell-McGovern, C. S.; Wiebe, D. J. (The American Journal of Sports Medicine, 2019)
Background: Little is known about the nature of concussion injury among university student-athletes, including concussion incidence and rates across sports, the mechanisms of injury, the type of activity during competition or practice, and the time to return to academics, return to sport, and symptom resolution. Purpose: To describe methods of the Ivy League-Big Ten Epidemiology of Concussion Study and first epidemiologic findings. Study Design: Descriptive epidemiology study. Methods: A prospective cohort study was conducted with data accrued through a surveillance system that was launched in the 2013-2014 athletic season. Surveillance continues to operate by detecting and collecting sport-related concussion (SRC) cases and non-SRC cases in addition to outcomes among university student-athletes. Results: A total of 1922 cases of SRC (649 women, 1004 men) among athletes from 27 sports, including varsity sports and club rugby, were enrolled during the 5 athletic seasons from 2013-2014 through 2017-2018. American football had the most cases (n = 495, 25.8%), followed by women`s rugby (n = 199, 6.2%), men`s ice hockey (n = 106, 5.5%), men's lacrosse (n = 105, 5.5%), women's soccer (n = 103, 5.4%), wrestling (n = 93, 4.8%), and men's soccer (n = 89, 4.6%), and women's ice hockey (n = 78, 4.1%). The highest overall concussion rates occurred in women`s lacrosse (1.35 concussions per 1000 athletic exposures [AEs]) and football (1.26 per 1000 AEs). Rates of concussion were generally higher during competition than practice and were highest during wrestling competition (4.06 per 1000 AEs) and second highest during football competition (3.68 per 1000 AEs). The median number of concussion symptoms was 7. Time to symptom resolution was longer for athletes with =7 symptoms versus <7 (P < .001) but did not differ across the 4 sports with rules comparable by sex and did not differ significantly between women and men (median, 8 vs 9 days, respectively). Women and men did not differ in days to return to academics, exertion activities, or competition. Conclusion: This multisite collaborative endeavor has produced a robust database yielding novel opportunities to better understand the epidemiology of concussion among university student-athletes participating in a variety of sports. Given the setting and number of cases, these findings add to our understanding of SRC and are the first of many that will be generated over the coming years from this large study that continues in its sixth year.